PENINJAUAN KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP AKTIFITAS KERJA KARYAWAN DI BERBAGAI PERUSAHAAN SECARA KAJIAN SISTEMATIK - Sinta Aprilia; Hibarkah Kurnia; Welly Teguh Setyawan; Enang Ashar; Anang Wahyudi (Industry Xplore, 2023)
Every employee needs occupational safety and health in carrying out their obligations to work in every company. Therefore, employers and employees must work together to create occupational safety and health. This study aims to identify the influence of occupational safety and health that has been carried out in various companies. This research method uses a systematic reflection method that takes articles from several national journals regarding occupational safety and health. The findings of this study are that occupational safety and health cannot be ignored from various fields of the company, because it is very risky to harm and harm the company's employees so actions are needed to make employees feel safe, comfortable, and healthy. The results of this study resulted in the dominant publisher year being 2020 with 4 articles, while the type of industry that carried out the most occupational safety and health procedures was the shipping industry with 3 articles. The contribution of this research hopes to be used as a reference for other researchers to make it easier to find articles related to occupational safety and health.